2018
DOI: 10.1111/ajo.12824
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approach to hysterectomy and barriers to using minimally invasive methods

Abstract: Minimally invasive approaches to hysterectomy have been shown to be safe, effective and have recovery advantages over open hysterectomy, yet in Australia 36% of hysterectomies are still conducted by open surgery. In 2006, a survey of Australian gynaecological specialists found the main impediment to increasing laparoscopic hysterectomy to be a lack of surgical skills training opportunities. We resurveyed specialists to explore contemporary factors influencing surgeons' approaches to hysterectomy; 258 (estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“… 8 The key focus therefore, rather than being between LH and RH, should instead be on reducing the OH rate to a minimum. Although there are only a few absolute contraindications for OH, the number of cases that are performed through open surgery is still high in some institutions and there has been much discussion how this could be reduced through greater surgical training 28 or centralisation of cases to hospitals and surgeons with high MIS rates. 29 A reduction in OH can also be achieved through reducing the number of conversions from LH/RH to a minimum.…”
Section: Discussionmentioning
confidence: 99%
“… 8 The key focus therefore, rather than being between LH and RH, should instead be on reducing the OH rate to a minimum. Although there are only a few absolute contraindications for OH, the number of cases that are performed through open surgery is still high in some institutions and there has been much discussion how this could be reduced through greater surgical training 28 or centralisation of cases to hospitals and surgeons with high MIS rates. 29 A reduction in OH can also be achieved through reducing the number of conversions from LH/RH to a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examined the relationships between surgical approach to hysterectomy and women’s quality of life, for both benign and oncologic conditions ( 14 19 ). Most studies compared laparoscopic and open abdominal surgery ( 9 – 13 ), while 1 study compared TLH, VH, and TAH ( 8 ), and 4 TLH versus RH, reviewed in Albright et al ( 20 ). These studies all concluded that minimally invasive surgical approaches were associated with better postoperative quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand reasons for this, we explored the views of both surgeons and patients. Among 285 Australian obstetrics and gynecology specialists, the dominating barrier to practicing less invasive surgery was a lack of surgical training and mentoring (9). Among women who had a hysterectomy in the previous 2 years, the majority (62%) followed their doctor's advice on the surgical approach, and very few (<15%) sought a second opinion (10).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we interviewed and surveyed Australian gynaecologists 27. It is apparent that Australian gynaecologists prefer to offer the hysterectomy through a vaginal approach; however, if a vaginal approach is infeasible, many resort to an open, abdominal surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate why TAH was still commonly used, a survey of Australian and New Zealand gynaecologists identified two main barriers impeding the uptake of TLH: (1) surgeons’ lack of procedural skills for TLH and (2) the limited availability of structured training and mentoring opportunities to assist practising surgeons to gain those skills 27. Women who have had a hysterectomy were surveyed and reported that they commonly follow the advice of their doctor with regards to the type of hysterectomy, and rarely reported to seek a second opinion 28…”
Section: Rationalementioning
confidence: 99%